Privatization of War – The Russian Mode Using the Wagner Group as an Example - Adam Olechowski; Jarosław Wiśnicki (Polish Political Science Yearbook)
Private armies and the mercenary profession associated with them are nothing new in the history of wars. The mercenary troops of Italian conditioners and German Landsknecht operating at the turn of the Middle Ages and the Renaissance even contributed to creating a romantic myth of mercenary soldiers. Even the French Revolution did not end private armies and mercenaries, which resulted in the creation of large, conscripted national armies. In the 21st century, we observe a renaissance of private armies. Military strategists are already talking about the privatization of war. This can be confirmed by the growing participation of private military corporations in armed conflicts in the 21st century. An example is the Russian Wagner Group at the forefront. The Wagner Group, as a tool in the hands of Russian authorities, participates not only in the war in Ukraine. The multifaceted activities and certain peculiarities in the functioning of the Wagner Group